2016
DOI: 10.3233/blc-150044
|View full text |Cite
|
Sign up to set email alerts
|

A Nonselective Cyclooxygenase Inhibitor Enhances the Activity of Vinblastine in a Naturally-Occurring Canine Model of Invasive Urothelial Carcinoma

Abstract: Background: Chemotherapy is expected to remain an important part of invasive urothelial carcinoma (UC) treatment. Strategies to enhance chemotherapy efficacy are needed.Objective: To determine the chemotherapy-enhancing effects of a nonselective cyclooxygenase (COX) inhibitor on vinblastine in a naturally-occurring canine model of invasive UC.Methods: With IACUC approval, privately-owned dogs with naturally-occurring histologically-diagnosed invasive UC, expected survival ≥6 weeks, and informed owner consent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 67 publications
(42 reference statements)
3
56
1
1
Order By: Relevance
“…A similar result was also obtained in the analysis that was conducted using female dogs alone to avoid the influence of prostate involvement, which was reported to be a negative prognostic factor in male dogs, thus, indicating urethral TCC itself might be a negative prognostic factor regardless of prostate involvement. Previous studies have reported that metastasis rates to the lung and bone at diagnosis were 6% to 29% and 8% to 10%, respectively . Our data showed that 35.4% and 24.6% of dogs had metastasis to the lung and bone, respectively.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…A similar result was also obtained in the analysis that was conducted using female dogs alone to avoid the influence of prostate involvement, which was reported to be a negative prognostic factor in male dogs, thus, indicating urethral TCC itself might be a negative prognostic factor regardless of prostate involvement. Previous studies have reported that metastasis rates to the lung and bone at diagnosis were 6% to 29% and 8% to 10%, respectively . Our data showed that 35.4% and 24.6% of dogs had metastasis to the lung and bone, respectively.…”
Section: Discussionsupporting
confidence: 51%
“…This retrospective study was designed to evaluate factors associated with ST and to compare characteristics between tumour localizations in dogs with urinary TCC that underwent whole‐body CT at diagnosis. Because bladder TCC involves the urethra in 56% to 58.8% of dogs and the prostate in 29% to 54.5% of male dogs, few studies have distinguished the characteristics of urethral TCC from that of bladder TCC . Our results revealed two major findings about the clinical behaviour and outcome of urethral TCC and new factors associated with ST. First, dogs with urethral TCC had higher metastasis rates at diagnosis and shorter ST than did dogs with bladder TCC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In canine prostatic carcinoma, both piroxicam and carprofen (a preferential COX‐2 inhibitor; this class of drugs affects both COX‐1 and COX‐2 but is more selective towards COX‐2) significantly increased survival time as single agents when compared to untreated dogs in both early stage and metastatic disease . As part of dual modality treatment and metronomic chemotherapy, piroxicam significantly increased survival time and incidences of complete or partial remission compared to the same treatments without piroxicam in a range of cancer types including invasive urothelial carcinoma and primary lung carcinoma . A recent review on canine mammary carcinoma concludes that including NSAIDs in treatment significantly improves survival, especially in inflammatory mammary carcinomas when NSAIDs are used alone as palliative treatment or in combination with chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Knapp et al (2016) noted that when vinblastine treatment was followed by piroxicam as two single agents there was a significant increase in overall survival time compared to dogs receiving the same agents simultaneously. It is suggested that this could be the consequence of drug resistance developing separately for each drug over time rather than concurrently, which raises the interesting possibility that chemotherapy may sensitize the tumour to the action of COX inhibitors . After chemotherapy treatment, resistant cells can go on to repopulate the tumour, a process that has been shown to involve the COX‐2 pathway .…”
Section: Discussionmentioning
confidence: 99%